Crystallization of the secondary alcohol dehydrogenase from Thermoanaerobacter ethanolicus 39E. - Arni, R. K.; Watanabe, L.; Fontes, M.; Burdette, D. S.; Zeikus, J. G. (Bentham Science Publ Bv, 1996)
The secondary alcohol dehydrogenase from the thermophile Thermoanaerobacter ethanolicus 39E has been crystallized at 40 degrees C by vapour difussion using polyethelene glycol as a precipitant. The orthorhombic crystals belong to the space group P 2(1)2(1)2 with cell constants of a=170.0 Angstrom, b=125.7 Angstrom and c=80.5 Angstrom. A native X-ray diffraction data set has been collected to 2.7 Angstrom resolution.